Mechanismen des nicht konventionellen RNA-Spleißens - Peschek, Jirka (Biospektrum, 2021)
The cellular pool of RNA is immensely diverse and complex. During their biosynthesis, RNA molecules undergo a vast number of co- and posttranscriptional processing and modification steps. A unique example of RNA processing is the non-conventional splicing of RNAs. This protein-catalysed splicing mechanism is an essential step during tRNA maturation and a main mode of endoplasmic reticulum (ER) stress signalling. Here, I discuss the cellular roles and catalytic machinery of non-conventional splicing in eukaryotes.